Is wave energy untapped potential?. (1st September 2021) - Terrero González, Alicia; Dunning, Peter; Howard, Ian; McKee, Kristoffer; Wiercigroch, Marian
Abstract: The increase of energy demand in the past 50 years and the targets to reach net-zero carbon dioxide emissions have led to an increase of electricity production from renewable energy sources. This paper first gives a snapshot of the word's energy mix and then reviews the most widely used renewable energy sources in the market; comparing their reliability, efficiency and cost-effectiveness, and highlighting their major advantages and weaknesses. The review concludes that marine energy, and specifically wave energy, can be the emerging energy source capable of addressing many of the problems that current renewable energy concepts and devices present, although major challenges remain. The paper is focused on the current global position of wave energy technologies in the market and under development in the past two decades, by looking at their status, reliability, energy generated, capacity installed and geographical locations. The current marine energy status of the main players, including France and South Korea, is compared with the rest of Europe and the wave energy status in Europe has been reviewed with an special interest in UK, as one of the major players, and Australia as a new emerging area of development. The main Wave Energy Converters (WECs) together with the world's wave energy density map are also discussed. This has led to a conclusion, that even though there is high energy potential, the wave technologies developed to date cannot offer a much needed breakthrough. A new concept of WEC based on a system of synchronized rotational pendula, having potential to work across-scales is introduced, which can motivate future work. Graphical abstract: Image, graphical abstract